Students’ listening comprehension problems and coping strategies in TOEFL tests - Syahabuddin, Khairiah; Sa'i, Sa'i; Azizah, Azizah; Faradhila, Faradhila; Al-Darary, Tijan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Listening comprehension is widely acknowledged as a critical component of second language proficiency, yet many learners continue to experience substantial difficulty in this skill, particularly in high-stakes assessment contexts such as the TOEFL. Despite its importance, research continues to highlight a gap in understanding the specific challenges faced by learners and the strategies they adopt to manage these demands. Accordingly, this study sought to explore the types of listening difficulties encountered by students during the TOEFL and to identify the strategies they employ to address them. Using a descriptive qualitative approach, data were collected from twenty undergraduate students who had previously taken the TOEFL through structured interviews and documentation analysis. The findings revealed several recurring challenges, including reduced concentration, unclear speaker voice, low audio quality, rapid delivery of speech, and unfamiliar vocabulary. Participants reported managing these difficulties through increased exposure and practice, maintaining stronger focus throughout tasks, utilizing top-down strategies such as identifying main ideas, and applying inferencing and prediction to anticipate information. Overall, the study illustrates the multifaceted nature of TOEFL listening challenges and emphasizes the value of explicit listening strategy instruction and regular practice within language programs. Future research involving more diverse learner populations is recommended to strengthen the generalizability and applicability of these findings.